The double-sided of human leukocyte antigen-G molecules in type 1 autoimmune hepatitis - Littera, Roberto; Perra, Andrea; Miglianti, Michela; Piras, Ignazio S.; Mocci, Stefano; Lai, Sara; Melis, Maurizio; Zolfino, Teresa; Balestrieri, Cinzia; Conti, Maria; Serra, Giancarlo; Figorilli, Francesco; et al. (Frontiers in Immunology, 2022)
The immunomodulatory effects of HLA-G expression and its role in cancers, human liver infections and liver transplantation are well documented, but so far, there are only a few reports addressing autoimmune liver diseases, particularly autoimmune hepatitis (AIH). Method and materials: We analyzed the genetic and phenotypic characteristics of HLA-G in 205 type 1 AIH patients (AIH-1) and a population of 210 healthy controls from Sardinia (Italy). Results: Analysis of the HLA-G locus showed no substantial differences in allele frequencies between patients and the healthy control population. The HLA-G UTR-1 haplotype was the most prevalent in both AIH-1 patients and controls (40.24% and 34.29%). Strong linkage was found between the HLA-G UTR-1 haplotype and HLA-DRB1*03:01 in AIH-1 patients but not controls (D’ = 0.92 vs D’ = 0.50 respectively; P = 1.3x10-8). Soluble HLA-G (sHLA-G) levels were significantly lower in AIH-1 patients compared to controls [13.9 (11.6 – 17.4) U/mL vs 21.3 (16.5 – 27.8) U/mL; P = 0.011]. Twenty-four patients with mild or moderate inflammatory involvement, as assessed from liver biopsy, showed much higher sHLA-G levels compared to the 28 patients with severe liver inflammation [33.5 (23.6 – 44.8) U/mL vs 8.8 (6.1 – 14.5) U/mL; P = 0.003]. Finally, immunohistochemistry analysis of 52 liver biopsies from AIH-1 patients did not show expression of HLA-G molecules in the liver parenchyma. However, a percentage of 69.2% (36/52) revealed widespread expression of HLA-G both in the cytoplasm and the membrane of plasma cells labeled with anti-HLA-G monoclonal antibodies. Conclusion: This study highlights the positive immunomodulatory effect of HLA-G molecules on the clinical course of AIH-1 and how this improvement closely correlates with plasma levels of sHLA-G. However, our results open the debate on the ambiguous role of HLA-G molecules expressed by plasma cells, which are pathognomonic features of AIH-1.